EXPLORING SOCIAL MEDIA AND CHILDREN’S DIGITAL CULTURE THROUGH CREATIVE METHODS - Mainsah, Henry (AoIR Selected Papers of Internet Research, 2026)
Social media platforms have become significant spaces where young people socialize and participate in public life. Young people face increasingly complex social, moral and ethical questions and dilemmas given the way interaction happens in these spaces. However, the rapid changes in technical functionalities of social media platforms, and evolving social norms within user communities, have increased the complexity and multiplicity of meaning-making and the digital literacies available within such environments. The study of digital culture in such contexts requires novel methods and techniques that can enable researchers to better examine the complexity of young people’s activities, experiences, and competencies. This paper explores the possibilities and affordances of a series of visual, narrative, and interactive methods to prompt young people to reflect on the nature of social media spaces and the norms that shape how they operate. This paper contributes to the growing volume of research on creative visual and arts-based methodologies for research on digital culture